PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KANTOR KECAMATAN TAGULANDANG KABUPATEN SITARO - Tatulus, Afny; Mandey, Jantje; Rares, Joyce (Sam Ratulangi University, 2015)
Abstract : The progress and setbacks of an organization depends on leadership qualities of a leader.Seen from the point of view of any leader is always placed on one very important point. The role of aleader in an organization or group is vital. Because in that role, a leader will help the organization torealize its vision and mission. the purpose of this research can be formulated as follows: To determinethe effect of Leadership Influence on Performance of Civil Servants in the District Office DistrictTagulandang Sitaro.This is a descriptive quantitative research, which describes the relationship between variables toanalyze numerical data using statistical methods through hypothesis testing. In this study took theentire population of employees at the District Office Tagulandang Sitaro Regency, North Sulawesi,which consists of 18 people.Results of simple correlation analysis showed that the leadership role positively and significantlycorrelated to the performance of an employee or significant influence with the power of 58.7%;meaning that developments in performance of 58.7% is determined or influenced by the leadershiprole.Keywords: Leadership, Performance